MAKING A SIMULATED AGREEMENT DEED BY A NOTARY AS THE CAUSE OF A LAND DISPUTE IN GIANYAR BALI (Case Study of Decision Number 259/Pdt.G/2020/PN. Gin) - Tama, Evan Mandala (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2024)
This study aims to analyze the making of simulated agreement deeds by notaries as the cause of land disputes in Gianyar, Bali. The main focus of this study is to examine the legal impact and potential conflicts that may arise due to the practice of making simulated agreement deeds. This research uses a normative juridical method, which is based on legal research through literature review. The results of the study show that the creation of a simulated agreement deed by a notary has the potential to cause land disputes, especially if it does not meet the applicable legal provisions. Factors such as the validity of the agreement, lack of clarity of information, and potential abuse of position can be a source of dissatisfaction and conflict among the parties involved. This research provides in-depth insight into the complexity of legal and social problems that can arise from the practice of making simulated agreement deeds. The implications of these findings show the need to improve the regulatory system and notary practices to prevent land disputes and increase public trust in the process of making deeds by notaries. The results of the study also stated that the deed of simulated agreement between David John Lock and Anak Agung Gede Oka Yuliartha was declared contrary to the law, so it was invalid, null and void, and did not have binding legal force. As a result of this agreement, the object of sale and purchase in the form of land covering an area of 200M2 and Certificate of Ownership Number: 2725/Desa Mas covering an area of 1,150 M2 became a dispute. The study also highlights the importance of a better understanding among notaries of the legal implications of creating simulated deed of agreement, as well as the need for stricter oversight to ensure that each deed made complies with applicable legal standards. Thus, this research is expected to make an important contribution to the development of notary law and the enforcement of justice in the settlement of land disputes.Keywords: Notary, Gianyar Bali, Preparation of Simulated Agreement Deed